Wiley International Encyclopedia of Marketing 2010
DOI: 10.1002/9781444316568.wiem04001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Marketing Communication

Abstract: [IMC is a] concept of marketing communications planning that recognizes the added value of a comprehensive plan that evaluates the strategic roles of a variety of communication disciplinesgeneral advertising, direct response, sales promotion, and public relations -and combines these disciplines to provide clarity, consistency, and maximum communication impact (Caywood, Schultz, and Wang, 1991b: 2-3).However, more recent definitions, such as the one presented by Schultz (2004a), add substantial value to old de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 118 publications
(222 reference statements)
0
28
0
4
Order By: Relevance
“…It has been suggested that few organisations achieve complete integration at the highest level (Kitchen and Burgmann, 2010) which means that not many companies have been able to benefit from all the advantages that IMC can offer. Luck and Moffatt (2009) state that this is because client organisations find the concept difficult to understand.…”
Section: Content Channels and Results Of Brand Communication Programs"mentioning
confidence: 99%
“…It has been suggested that few organisations achieve complete integration at the highest level (Kitchen and Burgmann, 2010) which means that not many companies have been able to benefit from all the advantages that IMC can offer. Luck and Moffatt (2009) state that this is because client organisations find the concept difficult to understand.…”
Section: Content Channels and Results Of Brand Communication Programs"mentioning
confidence: 99%
“…IMC is considered one of the most controversial areas of research, expert's opinions being found in a diverse range, whose amplitude includes very different approaches. There are point of views according with this concept is the most important development of marketing communications in the last decade of the twentieth century (Kitchen and De Pelsmacker, 2004) and views which assume that IMC does not go beyond a collection of specific concepts traditional marketing, presented in a new form (Spotts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, managers approach, articulate and implement their company's marketing communication strategies using integrated tactics. According to Kitchen and Burgmann (2010) and Kitchen et al (2004), marketing managers should consider integration of different marketing approaches not as part of their marketing-mix, but as a holistic concept. The concept chosen should employ all the elements of marketing-mix to promote and reinforce customer interactions and distribute integrated messages to the appropriate target audience.…”
Section: Introductionmentioning
confidence: 99%